2017
DOI: 10.1002/etc.3741
|View full text |Cite
|
Sign up to set email alerts
|

Returning to normal? Assessing transcriptome recovery over time in male rainbow darter (Etheostoma caeruleum) liver in response to wastewater‐treatment plant upgrades

Abstract: The present study measured hepatic transcriptome responses in male rainbow darter (Etheostoma caeruleum) exposed to 2 municipal wastewater-treatment plants (MWWTPs; Kitchener and Waterloo) over 4 fall seasons (2011-2014) in the Grand River (Ontario, Canada). The overall goal was to determine if upgrades at the Kitchener MWWTP (in 2012) resulted in transcriptome responses indicative of improved effluent quality. The number of differentially expressed probes in fish downstream of the Kitchener outfall (904-1223)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 75 publications
(176 reference statements)
0
10
0
Order By: Relevance
“…Total effluent estrogenicity followed a pattern similar to that of nitrogenous products over time. Recent studies showed that there were various pharmaceuticals detected in the Waterloo MWWTP effluent over time (2011–2015), further confirming that its quality remained extremely variable (Marjan et al ; Hicks et al ).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Total effluent estrogenicity followed a pattern similar to that of nitrogenous products over time. Recent studies showed that there were various pharmaceuticals detected in the Waterloo MWWTP effluent over time (2011–2015), further confirming that its quality remained extremely variable (Marjan et al ; Hicks et al ).…”
Section: Discussionmentioning
confidence: 87%
“…Consequently, this was associated with an approximately 10‐fold reduction of total effluent estrogenicity in 2015 compared with the pre‐upgrade period (2011). Moreover, pharmaceuticals such as naproxen and ibuprofen, which are considered to be reliable indicators of effluent quality and process changes (e.g., nitrification), also showed a significant reduction following the upgrades (Marjan et al ; Hicks et al ). For instance, Hicks et al () reported a 135‐fold reduction in ibuprofen and a 20‐fold reduction in naproxen in the post‐upgrade period compared with the pre‐upgrade period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentration limits for effects of CECs are difficult to set due to the potential synergistic, antagonistic, or additive effects of contaminant combinations [46,47]. Although concentrations have significantly decreased compared to pre-upgrade concentrations, they may still have the potential to cause sub-lethal effects on fish populations [12,48]. In the summer, there is a decrease in the flow in the river and this may be exposing the fishes downstream to a higher concentration of contaminants than in other seasons due to less dilution [49].…”
Section: Discussionmentioning
confidence: 99%
“…Responses documented at US2 and DS2 may indicate that fish were responding to other stressors upstream, such as non-point sources of agricultural and urban inputs. These inputs should be considered for future studies, as effects can be hard to differentiate from the MWWTP inputs [1,48]. ).…”
Section: Discussionmentioning
confidence: 99%